2015
DOI: 10.1002/jez.b.22622
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of oviparity in squamate reptiles: An adaptationist perspective

Abstract: Phylogenetically based analyses can suggest directions of evolutionary transitions, based on parsimony, but can never provide unambiguous answers. To clarify the relative frequency of phylogenetic shifts from oviparity to viviparity versus the reverse, we need additional sources of evidence. Adaptationist thinking (i.e., consideration of selective forces) has revealed a great deal about the transition from oviparity to viviparity, but has rarely been employed to consider the reverse transition. An evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 44 publications
0
39
0
1
Order By: Relevance
“…This finding is highly contrary to views based on previous reconstructions, and on physiological and developmental evidence. Thus, the findings of Pyron & Burbrink () have recently been highly criticized on methodological and biological grounds (Blackburn, ; Griffith et al ., ; King & Lee, ; Shine, ; Wright et al ., ). Pyron & Burbrink () also found that rates of speciation were higher for viviparous lineages than oviparous lineages, but differences in extinction rates led to net diversification rates that were lower for viviparous lineages, in contrast to previous studies within smaller squamate clades (Lynch, ; Lambert & Wiens, ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding is highly contrary to views based on previous reconstructions, and on physiological and developmental evidence. Thus, the findings of Pyron & Burbrink () have recently been highly criticized on methodological and biological grounds (Blackburn, ; Griffith et al ., ; King & Lee, ; Shine, ; Wright et al ., ). Pyron & Burbrink () also found that rates of speciation were higher for viviparous lineages than oviparous lineages, but differences in extinction rates led to net diversification rates that were lower for viviparous lineages, in contrast to previous studies within smaller squamate clades (Lynch, ; Lambert & Wiens, ).…”
Section: Introductionmentioning
confidence: 91%
“…Most of the responses to Pyron & Burbrink () have argued from physiological and developmental principles that multiple regains of oviparity are unlikely (Blackburn, ; Griffith et al ., ; Shine, ). Wright et al .…”
Section: Introductionmentioning
confidence: 99%
“…The placenta has evolved independently in at least 115 amniote lineages, with all but one of these transitions occurring in lizards and snakes (Blackburn 2014; Griffith et al 2015). While a recent analysis suggested that the number of independent origins of viviparity may be controversial, there is a consilience of data that counters any suggestion that there have been a high number of reversions from a viviparous to oviparous reproductive mode (Griffith et al 2015; Shine 2015; Wright et al 2015). The presentation of these data led the lead author of the original analyses to concede that the data support the hypothesis that there have been frequent transitions to viviparity in squamates (Pyron 2015).…”
Section: Introductionmentioning
confidence: 97%
“…When we submitted our manuscript (Pyron and Burbrink, ) on 2 May 2013, I did not anticipate how controversially it would be received, or the magnitude of the response. Articles in this issue (Blackburn, ,b; Duchêne and Lanfear, ; Griffith et al, ; King and Lee, ; Shine, ; Stewart, ; Wright et al, ) and in other journals (King and Lee, ) have re‐examined our data, analyses, and conclusions, drawing a wide range of inferences. Our summary (Pyron and Burbrink, ) was written before any of the responses appeared, and merely gives an overview of our original conclusions, with some suggestions for future research.…”
mentioning
confidence: 97%
“…Here, I take a final opportunity to digest the recent responses to Pyron and Burbrink (), and offer a complementary perspective. Future studies of parity‐mode evolution should consider the following four points: It is clear that transitions both from oviparity to viviparity, and any potential reversals from viviparity to oviparity, are physiologically complex and involve a multitude of genetic and developmental changes (Brandley et al, ; Blackburn, ; Shine, ). This fact should not be overlooked or glossed over by studies attempting to reconstruct these transitions (Lynch and Wagner, ; Fenwick et al, ; Pyron and Burbrink, ; Griffith et al, ).…”
mentioning
confidence: 99%